Pengaruh Kualitas Produk, Religiusitas, Kualitas Pelayanan, dan Promosi Terhadap Keputusan Mahasiswa Menabung di Bank Syariah - Melita Puji Pramudani; Annisa Fithria (Syi`ar Iqtishadi : Journal of Islamic Economics, Finance and Banking, 2021)
This study analyses the effect of product quality, religiosity, service quality, and promotion on student saving decisions at Islamic banks. This study uses 60 respondents as samples. This study uses purposive sampling to determine the samples with certain criteria. This study uses the multiple linear regression method to examine the effect of the independent variable on the dependent variable. The results indicate that product quality and promotion affect student saving decisions, but religiosity and service quality have no effect on student saving decisions.